Analisis Pengaruh Audit Investigatif Terhadap Pengungkapan Fraud - Aisyah Sekar Ningrum; Nanda Suci Handayani Umagap; Nera Marinda Machdar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The urgency in every scientific article is the author's knowledge of theory and previous research. Previous research can develop phenomena and theories involving correlation between variables. The purpose of writing this article is to develop a hypothesis of the influence between variables to be used in subsequent research. The findings from this literature review are: 1) investigative audits have a positive and significant effect on fraud disclosure.